Pengaruh Lingkungan Internal Dan Eksternal Organisasi Terhadap Kinerja Pegawai (Studi Pada Pegawai Di Kantor Otoritas Bandar Udara Wilayah VIII Manado) - Usman, Claudio; Liando, Daud; Rumawas, Wehelmina (JURNAL ILMIAH SOCIETY, 2016)
The work environment is divided into two, namely the internal environment and the external environment of the organization, where both can affect employee performance. Internal Environmental organizations often faced with a problem the mission, policies, organizational culture, information systems and individual differences of employees while the external environment, namely the labor force, legal regulation / legislation, society, technology, and economics. The purpose of this study is to analyze and explain the internal and external environment influence the organization of the performance of the staff of the Airport Authority Region VIII Manado.The method used is quantitative. The sampling technique used is the technique census. Samples taken amounted to 64 respondents. The analytical method used is multiple linear regression analysis. The hypothesis was tested by using statistical test F and test t statistic. From this study it can be concluded that there is a positive and significant effect either partially or simultaneously on the organization's internal and external environment on the performance of the staff of the Airport Authority Region VIII Manado. Suggestions in this research is necessary to improve the quality of existing services, and considering the work environment working conditions there, both from within and from outside so that the performance of employees may increase even more. Keywords: Internal environment, External environment, Performance